P Hubungan antara Kebutuhan Afiliasi dengan Kecenderungan Perilaku Prososial pada Mahasiswa - RR. Hesti Setyodyah Lestari; Ahmad Zahrul Khisom; Andia Kusuma Damayanti (Jurnal Bisnis Islam dan Kewirausahaan, 2024)
Prosocial behavior refers to genuine actions to provide assistance to others. The aim of this research is to explore the correlation between the need for affiliation and prosocial behavior tendencies within the Study Program Student Association at the Islamic State University of Raden Rahmat Malang (UNIRA Malang). This research method is quantitative with a correlational design, using accidental sampling techniques. A total of 134 student association members participated in this research. Data analysis was carried out using Pearson product moment correlation. The results of the research show that there is a very strong positive relationship (rxy = 0.857) between the need for affiliation and prosocial behavior in the UNIRA Malang Study Program Student Association. Thus, it can be concluded that there is a close relationship between the need for affiliation and prosocial behavior. The conclusion that can be drawn from this research is that the need for affiliation has a very strong positive relationship with prosocial behavior in the UNIRA Malang Study Program Student Association